Benign pericardial schwannoma with massive pericardial effusion in a Chinese man: A case report. Issue 10 (25th October 2019) - Li, Cuiling; Zhang, Jingwei; Fan, Rui; Chen, Lili; Liu, Donghong; Lin, Hong
Abstract: Primary cardiac neoplasms are rare, and the pericardial schwannoma has an even lower occurrence. We report a case of pericardial schwannoma in China, which is the eighth reported case adding to the existing literature on pericardial schwannoma, and this is the first case reported complicated with massive pericardial effusion. Pericardial schwannomas are usually benign, but they can sometimes have a malignant tendency and cause life‐threatening complications. Thus, it should be managed aggressively and completely resected.